Growth Performance, Digestive Enzymes, and TOR Signaling Pathway of Litopenaeus vannamei Are Not Significantly Affected by Dietary Protein Hydrolysates in Practical Conditions - Shao, Jianchun; Zhao, Wei; Liu, Xinwei; Wang, Lei (Frontiers in Physiology, 2018)
Protein hydrolysates have been widely reported as the protein source of aquatic feed. However, previous studies on protein hydrolysates focused on fish under experimental conditions. This study evaluated the potential for the replacement of fishmeal with protein hydrolysates in the diet of Litopenaeus vannamei under practical conditions. A 6-week feeding trail in green house was conducted to investigate the effects of partially replacing fishmeal by protein hydrolysates on growth performance, digestive enzymes and TOR signaling pathway of L. vannamei. 72,000 shrimps (initial body weight 2.26 ± 0.02 g) were randomly selected and placed in groups into 9 concrete tanks (L 5 m × W 5 m × H 1 m) (3 treatments × 3 replicates × 8000 individuals per concrete tanks). Two isonitrogenous (430 g kg-1) and isolipidic (80 g kg-1) diets were prepared: FM containing 400g kg-1 fishmeal and PH in which the fishmeal in FM was replaced by protein hydrolysates at 15%. A commercial diet (CD) was used as reference. Final weight (FW), percent weight gain (PWG), specific growth ratio (SGR), total weight for each tank (TW) of L. vannamei fed FM and PH diets were not significant differences (P > 0.05), while shrimp fed PH diet had significantly higher FW, PWG, SGR, TW values than those fed CD diet (P < 0.05). Trypsin activity was significantly lower in shrimp fed CD diet, than in shrimp fed FM and PH diets (P < 0.05). However, trypsin activity of L. vannamei fed FM and PH diets were not significant differences (P > 0.05). The mRNA expression of tor, s6k, 4e-bp gene were not significantly affected between FM and PH diets, while tor and s6k expression levels of CD diet were significantly down-regulated. Based on the above data, 15% replacement of fishmeal with protein hydrolysates did not make any difference on shrimps compared with FM group. Therefore, protein hydrolysates can partially replace fishmeal as the protein source of shrimp formula feed in practical conditions.